2021
DOI: 10.3390/ijms22084241
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD)—A Condition Associated with Heightened Sympathetic Activation

Abstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) is the most common liver disease affecting a quarter of the global population and is often associated with adverse health outcomes. The increasing prevalence of MAFLD occurs in parallel to that of metabolic syndrome (MetS), which in fact plays a major role in driving the perturbations of cardiometabolic homeostasis. However, the mechanisms underpinning the pathogenesis of MAFLD are incompletely understood. Compelling evidence from animal and human st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 137 publications
3
24
0
Order By: Relevance
“…A very recent study identified a liver-heart axis, showing that hepatocyte-derived, rather than locally synthesized, cardiac angiotensinogen, contributes to myocardial dysfunction in septic mouse models [11] . Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD [12] . This lipolytic state, induced by sympathetic overactivity, results in increased levels of FFAs and triglycerides in the circulation and visceral deposition, which exacerbates NAFLD.…”
Section: The Mechanisms Underlying Nafld-related Cvd Must Be Further ...mentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent study identified a liver-heart axis, showing that hepatocyte-derived, rather than locally synthesized, cardiac angiotensinogen, contributes to myocardial dysfunction in septic mouse models [11] . Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD [12] . This lipolytic state, induced by sympathetic overactivity, results in increased levels of FFAs and triglycerides in the circulation and visceral deposition, which exacerbates NAFLD.…”
Section: The Mechanisms Underlying Nafld-related Cvd Must Be Further ...mentioning
confidence: 99%
“…[11] Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD. [12] This lipolytic state, induced by sympathetic overactivity, results in increased levels of FFAs and triglycerides in the circulation and visceral deposition, which exacerbates NAFLD.…”
Section: Neuroendocrine Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that treatment with FABP4 exogenously induces endoplasmic reticulum stress in HepG2 liver cells as a potential link between hepatic insulin resistance and obesity-associated metabolic dysfunction 37 , suggesting that circulating FABP4 directly affects liver dysfunction, resulting in the development of MAFLD. Conversely, the condition of MAFLD might increase circulating FABP4 concentration through augmentation of catecholamineinduced lipolysis in adipose tissue, since chronic liver disease has been reported to increase sympathetic nervous system activation 38 . These findings indicate that circulating FABP4, derived from not only adipose tissue but also some hepatic cells, is one of the key modulators of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is regulated by both sympathetic and parasympathetic innervation, and the autonomic nervous system coordinates and regulates diverse hepatic physiology including glucose and liver metabolism, fluid balance, hepatic blood flow, bile flow, hepatic fibrosis and regeneration as well as circadian regulation of liver function ( Jensen et al, 2013 ; Amir et al, 2020 ; Ishay et al, 2021 ; Mizuno et al, 2021 ). The sympathetic nervous system has also been implicated in the pathophysiology of obesity, insulin resistance/metabolic syndrome ( Moreira et al, 2015 ; Guarino et al, 2017 ; Carnagarin et al, 2019 ; Russo et al, 2021 ; Yu and Lee, 2021 ), and emerging data from both pre-clinical and clinical studies suggest that sympathetic nervous system activation contributes to the development of NAFLD ( Carnagarin et al, 2021 ).…”
Section: Pharmacology Of Psychiatric Medications: Association With Me...mentioning
confidence: 99%